The Effect of Work Motivation and Organizational Culture on Job Satisfaction That Impact on Employee Productivity at PT. Reza Karya Abadi in Tangerang Selatan - Nurul Ilham (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of work motivation and organizational culture on job satisfaction which has an impact on employee productivity at PT Reza Karya Abadi in South Tangerang. The method used is explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study work motivation has a significant effect on job satisfaction by 38.9%, hypothesis testing obtained a significance of 0.000 <0.05. Organizational culture has a significant effect on job satisfaction by 42.6%, hypothesis testing obtained a significance of 0.000 <0.05. Work motivation and organizational culture simultaneously have a significant effect on job satisfaction by 52.2%, hypothesis testing is obtained a significance of 0.000 <0.05. Job satisfaction has a significant effect on employee productivity by 28.3%, hypothesis testing obtained a significance of 0.000 <0.05.